Association between changes in platelet reactivity during elective percutaneous coronary intervention and periprocedural myocardial infarction: A pilot study. Issue 2 (February 2019) - Kawai, Yusuke; Miyoshi, Toru; Nakamura, Kazufumi; Shokoku, Gentaro; Yamamoto, Keisuke; Ono, Tamaki; Tokioka, Kouji; Ohe, Tohru; Ito, Hiroshi
Highlights: Platelet reactivity is significantly increased after elective PCI. Increase in platelet reactivity is involved in peri-procedural myocardial damage. Increase in platelet reactivity is associated with lesional or procedural factors. Abstract: Background: High platelet reactivity before percutaneous coronary intervention (PCI) reportedly increases the risk of PCI-related myocardial infarction (PMI) following elective PCI. We conducted a pilot study to evaluate changes in platelet reactivity during PCI and their association with the incidence of PMI. Methods: In total, 133 consecutive patients undergoing elective PCI after pretreatment with dual antiplatelet therapy for at least 7 days were prospectively enrolled. Platelet reactivity was measured by the VerifyNow ® assay (International Technidyne Corporation, Edison, NJ, USA) immediately before and after PCI. Results: Platelet reactivity significantly increased from 177.3 ± 53.4 P2Y12 reaction units (PRU) before PCI to 203.4 ± 52.8 PRU immediately after PCI ( p  < 0.001). Absolute changes in platelet reactivity were significantly greater in patients with than without PMI (32.4 ± 29.0 vs. 21.2 ± 24.8 PRU, respectively; p  = 0.021). In the multivariable logistic regression analysis, the absolute change in PRU was an independent predictor of the incidence of PMI. Receiver operating characteristic curve analysis of the change in PRU during PCI for discriminating PMI showed a sensitivity, specificity, and the cut-off value of 46%, 76%, and 37 PRU, respectively (area under the curve = 0.607, p  = 0.0235). When the patients were divided into two groups, namely a greater (change in PRU ≥ 37) and smaller (change in PRU < 37) increase group, the incidence rate of PMI was significantly higher in the greater than smaller increase group (59.1% vs. 34.8%, respectively; p  = 0.008). Additional exploratory analyses by intracoronary imaging demonstrated that the proximal reference lumen area in the greater increase group was significantly smaller than that in the smaller increase group (6.5 ± 2.4 vs. 7.7 ± 3.1 mm 2, respectively; p  = 0.032). Conclusion: An increase in platelet reactivity after elective PCI is possibly associated with PMI. This finding should be validated by a larger-scale study.